Sistemas de informação na comercialização do café em uma cooperativa agrícola no Sul de Minas Gerais - Mello, Ricardo Bernardes de (2014)
This paper analyzes, through a descriptive research, technological profile of coffee farmers, cooperative members of CAPEBE. This analysis was needed by the growing use of technology, by virtually all sectors of the world economy. The main purpose of this research is to know how much the use of information systems is present in the lives of producers. The purpose was achieved through a field survey conducted with 104 members. The study showed that about 60% of respondents have a computer, but still, the use of information systems is limited because the vast majority done manually administrative routines of the property. It was observed that about 59% of the properties have access to the internet and the most widely used type of connection is via radio. The survey also revealed that the technology being used by them, to aid the routines of the property, is the use of smartphones. About 76% of the public agree that the use of technology to coffee marketing can ensure a better price. The study showed the need for prudence in meeting with technological resources to marketing of coffee. The cooperative still need further training for use of information systems in its properties as well as the cooperative can´t leave providing services over the Internet without knowing your target audience (cooperative) even if they are adjusting due to competition from other cooperatives.